Relevansi dan Implementasi Pemikiran Nurcholish Madjid terhadap Politik Indonesia - M Munawar (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2019)
This paper is based on a literature study that aims to examine the relevance and implementation of Islamic politics in the political arena of Indonesia, the majority of which are Muslims. The results of the study concluded that in the era of 70s emerged ??Nurcholish Madjid's idea that